Comparative studies on in vitro microrhizomeinduction in three varieties of Curcuma longa (Turmeric) – The role of two stress hormones - Indira Balachandran, Archana Cheethaparambil* , Geetha S. Pil (International Journal of Scientific Research and Management (IJSRM), 2013)
Turmeric- Curcuma longa L. of zingiberaceae, is one of the major medicinal spice crop in India. Microrhizome induction is a novel biotechnological tool to produce disease free planting materials in this rhizomatous crop since other crop improvement programmes are failed due to low seed set. Pathogen free nature and the genetic stability of the resultant plantlets/ rhizomes increase the acceptance in the commercialization of this technique. In the present study disclosed an efficient method for enhanced microrhizome production in three high yielding varieties of turmeric